1989
DOI: 10.1177/000841748905600409
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Use of Theory among Occupational Therapists: A Canadian Survey

Abstract: Recent interest M occupational therapy theory has focussed attention on the utility of theory for clinical practice and for research. However, for many therapists, knowledge and use of theory have changed notably since their educational days, and the process of keeping up to date on theory development may be difficult. Thi s paper presents the results of a survey aimed at identifying the extent of use of theory and the level of knowledge about theory among practicing therapists in Canada. A random sample of 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 5 publications
2
28
1
Order By: Relevance
“…It has been well documented in the literature that occupational therapy practitioners tend to resist demands for accountability in explaining how they use theory as a guide to clinical decision-making (Cole & Tufano, 2008;Du Toit & Wilkinson, 2011;Ikiugu, 2012;Law & McColl, 1989;O'Neal et al, 2007). Unfortunately, deemphasis of theory as a guide to practice may be detrimental to the well-being of the profession (Hinojosa, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented in the literature that occupational therapy practitioners tend to resist demands for accountability in explaining how they use theory as a guide to clinical decision-making (Cole & Tufano, 2008;Du Toit & Wilkinson, 2011;Ikiugu, 2012;Law & McColl, 1989;O'Neal et al, 2007). Unfortunately, deemphasis of theory as a guide to practice may be detrimental to the well-being of the profession (Hinojosa, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Javetz and Katz (1989) found that therapists selected models according to the perceived relevance of the model to their practice specialty areas (e.g., physical disabilities, pediatrics, mental health, and geriatrics). Law and McColl (1989) found evidence in support of the conclusion that the value therapists attached to theory, along with their knowledge of particular theories, was a major determinant of their selection and use of a theory.…”
Section: Review Of the Literaturementioning
confidence: 75%
“…Similarly, Law and McColl (1989) found that fewer therapists actually used theories (65.8%) than those who reported valuing theory (91%). These two studies suggest that therapists' attitudes are not the primary influence on whether they choose to use theory in practice.…”
Section: Review Of the Literaturementioning
confidence: 90%
See 2 more Smart Citations